2023
DOI: 10.1126/sciadv.adi7638
|View full text |Cite
|
Sign up to set email alerts
|

Direct observations of melting, freezing, and ocean circulation in an ice shelf basal crevasse

Peter Washam,
Justin D. Lawrence,
Craig L. Stevens
et al.

Abstract: Ocean conditions near the grounding zones of Antarctica’s ice shelves play a key role in controlling the outflow and mass balance of the ice sheet. However, ocean observations in these regions are largely absent. Here, we present a detailed spatial survey collected with an underwater vehicle in a basal crevasse located in the ocean cavity at the Ross Ice Shelf grounding zone. The observations depict fine-scale variability in ocean forcing that drives asymmetric melting along the lower crevasse sidewalls and fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 80 publications
(138 reference statements)
0
5
0
Order By: Relevance
“…The older fractures show considerable basal melt and widening compared with younger ones. Elevated water velocities within fractures have been observed below Thwaites Ice Shelf ( 25 ) and Kamb Ice Stream ( 30 , 31 ), which can explain the enhanced melting. However, it is also possible that the relatively warm and buoyant meltwater mixtures formed in the cavity ( Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The older fractures show considerable basal melt and widening compared with younger ones. Elevated water velocities within fractures have been observed below Thwaites Ice Shelf ( 25 ) and Kamb Ice Stream ( 30 , 31 ), which can explain the enhanced melting. However, it is also possible that the relatively warm and buoyant meltwater mixtures formed in the cavity ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Basal channels, stretching many kilometers (10,26,27), have been linked to enhanced basal melt (28). Elevated melt rates and decimeter-scale scallops have been observed on the steep sides of basal fractures (25,(29)(30)(31). Analysis of these processes has been limited by a lack of data from the ice base, particularly high-resolution surveys and complementary datasets covering sufficiently large areas to understand the extent and representativeness of the features.…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies continue to emphasize the intricate interplay between basal melt and crevasses (Alley et al, 2021;Washam et al, 2023). Similarly, Larter (2022) recently suggested that roughness may serve as a health indicator for ice shelves.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, where strain rates are high, the ice will fracture, causing crevasses (and potentially rifts) to form. Melt and fracture may also work in combination, where high melt rates increase the stress (Vaughan et al, 2012), resulting in crevasses, and/or basal melt erodes existing crevasses (Washam et al, 2023). The combined effect of these processes could increase roughness and potentially decrease ice stability.…”
Section: Journal Of Geophysical Research: Earth Surfacementioning
confidence: 99%
“…We find the maximum seawater intrusion distance dependent on C d , which is the measurable drag coefficient of water flowing past ice. Estimates of C d for the ice‐ocean interface are typically between 0.001 and 0.01 (Johannessen, 1970; Kottmeier & Engelbart, 1992; Lu et al., 2011; McPhee, 1989; Shirasawa, 1986), with C d values calculated directly from observations under ice shelves falling within this range (Washam et al., 2023). Using the end member values of C d , we find seawater intrusion to range from 1.5 to 15 km.…”
Section: Methodsmentioning
confidence: 99%